If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(L + 12) = 36 Reorder the terms: 2(12 + L) = 36 (12 * 2 + L * 2) = 36 (24 + 2L) = 36 Solving 24 + 2L = 36 Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 2L = 36 + -24 Combine like terms: 24 + -24 = 0 0 + 2L = 36 + -24 2L = 36 + -24 Combine like terms: 36 + -24 = 12 2L = 12 Divide each side by '2'. L = 6 Simplifying L = 6
| 3y+2=1-7y | | X-2.4=5.1 | | (p-4)(p+3)=0 | | 16cos^4(x)-12cos^2(x)+1=0 | | 68=t+(-14) | | Z-15=30 | | u-(-14)=19 | | 4*[1-(4-15)/3] | | 6i(4+2i)=equation | | (b-5)(2b-1)=0 | | 5(x+1)-x=4x+5 | | Y(9+y)=y*9+y*y | | -(2n+2n)= | | n+1n-5=0 | | 6i(4+2i)= | | 12x^2+3x-144=0 | | 5x-2(0)=9 | | p-4p+3=0 | | 6x^2+3x-144=0 | | 7(3y-6)=21 | | -10-5x^2=-350 | | k/-9=(-9) | | X*15=4 | | p/(-3)=(-10) | | 5(-4)-2y=9 | | 2x+6x-45=9 | | -2x-32=4(x+5)-4 | | 3x+7=4(2x-2) | | 2a-3(a-5)=5 | | k-(-71)=74 | | c-78=(-10) | | 9x^2=-77+18x |